2020
DOI: 10.3390/pharmaceutics13010010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diphenyleneiodonium Chloride on Intracellular Reactive Oxygen Species Metabolism with Emphasis on NADPH Oxidase and Mitochondria in Two Therapeutically Relevant Human Cell Types

Abstract: Reactive oxygen species (ROS) have recently been recognized as important signal transducers, particularly regulating proliferation and differentiation of cells. Diphenyleneiodonium (DPI) is known as an inhibitor of the nicotinamide adenine dinucleotide phosphate oxidase (NOX) and is also affecting mitochondrial function. The aim of this study was to investigate the effect of DPI on ROS metabolism and mitochondrial function in human amniotic membrane mesenchymal stromal cells (hAMSCs), human bone marrow mesench… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Further inhibition of NADPH oxidase activity by DPI or VAS2870 attenuated mtROS production, demonstrating an upstream role of NADPH oxidase in mtROS activation. Recent studies have also reported crosstalk between these two producers [39,[48][49][50]. Indeed, a previous study showed that the mitochondrial inner membrane was still intact, and there was no significant change in the composition of electron transport chain complexes in isolated mitochondria after acute heat treatment [26].…”
Section: Discussionmentioning
confidence: 99%
“…Further inhibition of NADPH oxidase activity by DPI or VAS2870 attenuated mtROS production, demonstrating an upstream role of NADPH oxidase in mtROS activation. Recent studies have also reported crosstalk between these two producers [39,[48][49][50]. Indeed, a previous study showed that the mitochondrial inner membrane was still intact, and there was no significant change in the composition of electron transport chain complexes in isolated mitochondria after acute heat treatment [26].…”
Section: Discussionmentioning
confidence: 99%
“…Diphenylammonium chloride (DPI) and N-acetylcysteine (NAC) are NADPH oxidase inhibitors and ROS scavengers, respectively, both of which reduce intracellular ROS levels [ 115 , 116 ].Silveira et al found that DPI and NAC treatment reduced the number of inflammatory cells and ROS levels in the lungs of OVA-challenged mice, in addition to reducing airway levels of released EETs [ 117 ]. However, as mentioned above, not all stimuli are dependent on the PAD4 mechanism, and the necessity of NADPH enzymes for EETs formation is controversial.…”
Section: Therapeutic Targets For Eetsmentioning
confidence: 99%
“…Its chemical nature makes DPI a potent inhibitor of flavin bearing oxidoreductases, which are generally an integral element of electron transport chains. DPI have a wide spectrum of known cellular targets including CPR [13,15,23], NADPH oxidase (NOX) [24][25][26][27][28][29][30][31], mitochondrial respiratory chain complex I (NADH ubiquinone oxidoreductase) [28,[32][33][34], and different types of nitric oxide synthase [13,35]. It is assumed that DPI inhibition is achieved by covalent modification of flavin and/or heme prosthetic groups within enzymes based on radical formation.…”
Section: Introductionmentioning
confidence: 99%